קום קרא: בין רומן לאנטי-רומן - בן לולו אילה (מכאן, 2021)
The character of the narrator in the novel Tolle Lege refers to himself as ״I that is, I." This article attempts to unravel this figure, the reasons for his disappearance or the metamorphosis that he undergoes, and his relationship with his fellow characters in the novel.